Modelo de um framework para o estabelecimento da criticidade - Belmonte, Danillo Leal (2007)
Traditionally, the criticality establishment of productive processes face some difficulties with respect to the monitoring. Most of the times, professionals define the periodicity and the types of maintenances based only on tacit knowledge and/or through computer applications that would help on this management. Such applications are generally bound to a proprietary operational system, resulting in costly solutions; additionally they lack flexibility and, generally, implement only one productive process manager method, leaving the professional without any possibilities to improve the final answer about the type of maintenance to be performed. The objective of this work was to create a framework model for the criticality establishment domain, addressing the issues mentioned. The proposed model for the criticality establishment implements attributes that makes easy to add methods that wasn't considered during the initial construction. Its also was developed with non proprietary and open-source tools, allowing other researches to propose improvements or its use as model in another works of the area. It provides the use of several methods, as well the combination and/or the addition of new ones, improving the precision of the maintenance type to be performed. The proposed model solution attributes - portability, reusability and flexibility, allows professionals to customize application for different application domains.